Enhanced sensitivity of microring resonator-based sensors using the finite difference time domain method to detect glucose levels for diabetes monitoring - Hasanah, Lilik; Nugroho, Harbi Setyo; Chandra, Wulandari; Budi, Mulyanti; Berhanuddin, Dilla Duryha; Mohamad Hazwan, Haron; Susthitha, Menon P.; Ahmad Rifqi, Md. Zain; Hamidah, Ida; Khairurrijal, Khairurrijal; R., Mamat (MDPI, 2019)
The properties of light and its interaction with biological analytes have made it possible to design sophisticated and reliable optical-based biomedical sensors. In this paper, we report the simulation, design, and fabrication of microring resonator (MRR)-based sensors for the detection of diabetic glucose levels. Electron Beam Lithography (EBL) with 1:1 hydrogen silsesquioxane (HSQ) negative tone resist were used to fabricate MRR on a Silicon-on-Insulator (SOI) platform. Scanning Electron Microscopy (SEM) was then used to characterize the morphology of the MRR device. The full-width at half-maximum (FWHM) and quality factors of MRR were obtained by using a tunable laser source (TLS) and optical spectrum analyzer (OSA). In this paper, the three-dimensional Finite Difference Time Domain (3D FDTD) approach has been used to simulate the proposed design. The simulation results show an accurate approximation with the experimental results. Next, the sensitivity of MRR-based sensors to detect glucose levels is obtained. The sensitivity value for glucose level detection in the range 0% to 18% is 69.44 nm/RIU. This proved that our MRR design has a great potential as a sensor to detect diabetic glucose levels.